Considering the Potential of Pesantren’s Constribution in Diversion Programs for Juvenile Offenders - Nuqul, Fathul Lubabin; Ningrum, Ardana Reswari Miranda (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS); Vol 1 No 1 (2020): 1st International Conference on Engineering, Technology, and Social Sciences (ICONETOS)DO - 10.18860/iconetos.v1i1.1151, 2020)
Diversion, in the Law of the Republic of Indonesia No. 11 of 2012 concerning the Juvenile Justice System, aims to save the future of children (victims and perpetrators). In the process diversion involves the community in the process of restoration of relations between victims and perpetrators. Diversion is carried out bearing in mind that children who are perpetrators of crime have the right to be treated fairly by the United Nations Convention on the Rights of the Child in 1989. The problem in the current diversion is the stigmatization of society and the rejection of perpetrators and their families. To overcome this, a selter is needed for adequate coaching. The existence of selter and competent social workers who handle is still very less when compared with the existing needs. Is an Islamic boarding school as an educational institution in Indonesia, has made many contributions in the development of social society in Indonesia. Not only religious education, the role of pesantren also contributes to the development of community skills, poverty alleviation, empowerment and other behaviorbased activities. Islamic boarding school education applies a live in system, which makes students (santri) live in a dormitory. With a system like this pesantren must have adequate facilities such as dormitories, places to study and mosques. Data from the Directorate of Islamic Education (Pendis) Ministry of Religion of the Republic of Indonesia, recorded 27,230 pesantren with various models (salaf and modern) that have accommodated 3,759,198 santri, both male and female. This number illustrates that pesantren has the potential to contribute to the handling of child offenders. Contribution of pesantren can be in the form of shelter and guidance for children of perpetrators. Some potential reasons that pesantren are alternative places to carry out diversion programs: 1) in large quantities and spread throughout Indonesia 2) have adequate facilities and human resources for mental development; 3). tested in a mental development program; 4). Community trust in pesantren is quite high. Before the pesantren becomes an alternative, there are a number of things that need to be addressed, among others: 1) aligning the vision of diversion between the legal apparatus and the boarding school administrators; 2) readiness of other pesantren residents (santri and teachers) to accept child crime perpetrators. 3) improvement of coach / teacher skills in handling child offenders.